Rancang Bangun Prototype Ayunan Bayi Berbasis Internet of Things - Balqis, Ratu; Husaini, Husaini; Anwar, Anwar (Politeknik Negeri Lhokseumawe, 2023)
The design uses a DC motor as a driving force. Sound sensor and motion sensor as input, wemos D1 as control center.An android phone with the blynk application as a regulator, and a wifi network as a liaison between the cellphone and wemos D1 to read motion settings from an android cellphone via blynk or read the value of the sound or motion sensor. The purpose of this research is to produce a system that works automatically on baby swings where the baby's swing is controlled remotely, thus easing mothers to put their babies to sleep. The method used in controlling the swing is the blynk application method. The swing time is according to the specified delay, the swing stops when the time runs out. The average score when there is no sound is 343, while 345 when there is sound Keywords: Wemos D1, PIR Sensor, Sound Sensor, DC Motor, L298N Motor Driver, and Android